Development and Prospects of Manifold Microchannel Heat Sink Research - Zhu Xunyi; Chen Chaowei; Zhang Jingzhi; Xin Gongming (Zhileng xuebao)
With rapid development of electronic devices, modern electronic devices require higher power and exhibit more heat flow density. Consequently, their thermal management requirements have increased drastically. Manifold microchannel heat sinks are considered as the optimal cooling technology for electronic devices due to their high heat dissipation capability, simplicity, and reliability. This paper describes the heat dissipation principles and advantages of manifold microchannel heat sinks and reviews relevant research about their geometrical parameters and optimal structures. It also provides an outlook on their future development.